A new species of Prosopocoilus Hope & Westwood, 1845 from China and Vietnam (Coleoptera: Lucanidae: Lucaninae) - Wang, Cheng-Bin; Wang, Yu (Zootaxa, 2021)
A new species of stag beetle, Prosopocoilus zhuchuangi new species (Coleoptera: Lucanidae: Lucaninae) is described from China (Guizhou) and Vietnam. It is closely related to P. fulgens (Didier, 1927), sharing a fringe of dense setae in the apical 2/3 of the mesal sides of the mesotibiae and metatibiae. Diagnostic characters of the two species are illustrated and compared.